Seasonal variation in the quality of dissolved and particulate organic matter exchanged between a salt marsh and its adjacent estuary. Issue 7 (28th July 2015) - Osburn, Christopher L.; Mikan, Molly P.; Etheridge, J. Randall; Burchell, Michael R.; Birgand, François
Abstract Fluorescence was used to examine the quality of dissolved and particulate organic matter (DOM and POM) exchanging between a tidal creek in a created salt marsh and its adjacent estuary in eastern North Carolina, USA. Samples from the creek were collected hourly over four tidal cycles in May, July, August, and October 2011. Absorbance and fluorescence of chromophoric DOM (CDOM) and of base‐extracted POM (BEPOM) served as the tracers for organic matter quality while dissolved organic carbon (DOC) and base‐extracted particulate organic carbon (BEPOC) were used to compute fluxes. Fluorescence was modeled using parallel factor analysis (PARAFAC) and principle components analysis (PCA) of the PARAFAC results. Of nine PARAFAC components (C) modeled, C3 represented recalcitrant DOM and C4 represented fresher soil‐derived source DOM. Component 1 represented detrital POM, and C6 represented planktonic POM. Based on mass balance, recalcitrant DOC export was 86 g C m−2 yr−1 and labile DOC export was 49 g C m−2 yr−1; no planktonic DOC was exported. The marsh also exported 41 g C m−2 yr−1 of detrital terrestrial POC, which likely originated from lands adjacent to the North River estuary. Planktonic POC export from the marsh was 6 g C m−2 yr−1. Assuming the exported organic matter was oxidized to CO2 and scaled up to global salt marsh area, respiration of salt marsh DOC and POC transported to estuaries could amount to a global CO2 flux of 11 Tg C yr−1, roughly 4% of the recently estimated CO2 release for marshes and estuaries globally.